Cognitive semantics : meaning and cognition - Allwood, Jens S., 1947-; Gärdenfors, Peter (Pragmatics & beyond ;, 1999)
Toward the end of the 20th century, there is both a dissatisfaction with existing formal semantic theories and a wish to preserve insights from other semantic traditions. Cognitive semantics, the latest of the major trends which have dominated the century, attempts to do this by focusing on meaning as a cognitive phenomenon. This book provides different perspectives on meaning as a cognitive phenomenon. Jens Allwood presents an approach where meaning is analyzed in terms of context sensitive cognitive operations. Peter Gärdenfors examines the relationship between cognitive semantics and standa.